Growth and photosynthetic pigments of passion fruit (Passiflora edulis) seedlings under foliar fertilization with nitrogen and irrigated with saline water - Micaela Benigna Pereira; Jackson Silva Nóbrega; Reynaldo Teodoro de Fátima; Jean Télvio Andrade Ferreira; Francisco Romário Andrade Figueiredo; Maria de Fátima de Queiroz Lopes; João Everthon da Silva Ribeiro; Walter Esfrain Pereira (Dyna, 2022)
In the semiarid region of Brazil, salts found in water used in irrigation. The objective of was to analyze the influence of foliar fertilization with nitrogen as a mitigation of the salt stress of passion fruit seedlings. The design was randomized blocks, with the treatments generated from the Box’s Central Composite matrix, with five electrical conductivities of irrigation water (ECw) (0.50; 0.98; 2.15; 3.32; 3.80 dS m-1) and five doses of foliar nitrogen fertilization (0.0; 0.30; 1.15; 1.97; 2.30 g L-1), with four replicates. The growth and photosynthetic pigments were evaluated Application of nitrogen doses attenuated the effect of salinity on morphophysiological aspects of passion fruit seedlings. The increase in the salinity of the water caused negative effects on the characteristics the growth and photosynthetic pigments